Flores hermafroditas de Quercus glaucoides Mart. & Gal. (Fagaceae) en el estado de Michoacán, México - Romero Rangel, Silvia; Rojas Zenteno, Ezequiel Carlos; Gómez Maqueda, Silvia (Instituto de Ecología, A.C., 2000)
Hermaphroditic flowers are reported from a population of Quercus glaucoides Mart. & Gal., located in the municipality of Nuevo Urecho, Michoacán. Floral structure is described and photographs and drawings obtained with light and scanning electron microscopes, are presented.